English Learning Challenges among Islamic Religious Education Students in Pesantren-Based Universities: A Contextual EFL Perspective - Johara Indrawati (Literaturia: Journal of Linguistics, Literature, and Language Teaching, 2026)
English language proficiency is increasingly important in teacher education programs, as it enables prospective teachers to access global pedagogical knowledge and engage in professional learning communities. However, non-English majors at faith-based institutions often face challenges in learning English. This qualitative study examines the English language learning challenges experienced by Islamic Religious Education (PAI) students at a pesantren-based university in Indonesia. Using semi-structured interviews, reflective writing, and classroom observations involving 24 PAI students, the study employed thematic analysis to explore linguistic difficulties, contextual barriers, and tensions between English language learning and professional identity formation. Using semi-structured interviews, reflective writing, and classroom observations involving 24 PAI students, the study employed thematic analysis to explore linguistic difficulties, contextual barriers, and tensions between English language learning and professional identity formation. The findings suggest that challenges to learning English extend beyond linguistic limitations to include institutional marginalization of English, limited disciplinary relevance, and a hierarchical language ideology that prioritizes Arabic over English. These challenges influence students' motivation and perceptions, as they consider English secondary to their future teaching roles. This study advocates for a contextualized English as a Foreign Language (EFL) approach to teacher education, proposing an English for Islamic Teacher Education orientation that aligns language learning with Islamic pedagogical practices. Implications for teacher educators, curriculum developers, and policymakers seeking to develop linguistically inclusive and contextually sensitive teacher education programs are discussed.